FOR PROMOTION AND CONTROL, SOCCER ABSORBS THE COUNTRYSIDE OF SAO PAULO - Kupper, Agnaldo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2020)
It is necessary to understand how the appropriation of soccer has been processed among those who have transformed it in a way to meet personal, familiar, and group goals. We cannot deny that, particularly in Brazil, the soccer practice is embedded in social relations and, consequently, subject to new participations and new meanings. Therefore, it is part of the changes engendered by the country's historical process. Favoring the ball game has brought benefits, both for those who have appropriated themselves as a source of leisure and for those who have benefited from their personal, familiar, commercial and/or political interests.
Keywords: Soccer; sponsorships; benefits and dividends